Reforms to the Country Administrative Division in Albania After 1990 - Hysi, Arben (Richtmann Publishing, 2012)
Political changes after 1990 necessitated the reorganization and functioning of local government in Albania. As it is known, twolevels of local government function in our country; the first level includes the communes and municipalities, while the second levelincludes the prefectures and counties. At the time being 12 counties and 12 prefectures, 36 districts, 65 municipalities, 309 communesand 3020 villages function in Albania. The functioning of local government is based on: Constitution of the Republic of Albania, Albanianlegislation since 1990 , especially the law no. 8652 which dates back to July 31, 2000